Substitution Garden and Polyethylene Terephthalate (PET) Plastic Waste as Refused Derived Fuel (RDF) - Zahra, Nurulbaiti Listyendah; Septiariva, Iva Yenis; Sarwono, Ariyanti; Qonitan, Fatimah Dinan; Sari, Mega Mutiara; Gaina, Pratiwi Claudia; Ummatin, Kuntum Khoiro; Arifianti, Qurrotin Ayunina Maulida Okta; Faria, Niswatun; Lim, Jun-Wei; Suhardono, Sapta; Suryawan, I Wayan Koko (International Journal of Renewable Energy Development, 2022)
The generation of polyethylene terephthalate (PET) plastic and garden waste must be recycled to support the circular economy. An alternative way to reduce the plastics waste is to reduce this waste by converting it into energy such as Refused Derived Fuel (RDF) as an alternative for processing waste. Substitution of plastic and garden waste is an opportunity to be analyzed. Hence, This study aimed to investigate the potential for converting material substitution from PET and garden waste into RDF. The RDF characterized test method was carried out by proximate, water content, ash content, and analysis. At the same time, the calorific value. was tested by bomb calorimetry. Substitution of the mixture of plastic and garden waste affects each parameter of RDF pellet quality including water, ash, and caloric value (sig.< 0.05). The increase of plastic waste in pellets consistently increases the calorific value of RDF from 18.94 until 25.04 MJ/kg. The RDF pellet water and ash content also invariably affect the rate of increase in the calorific value of RDF in the multilinearity model (sig.<0.05; R2 is 0.935). The thermal stability of the pellets occurred at a temperature of 5000C decomposition of hemicellulose, cellulose, and lignin in mixed garden waste with plastic in RDF pellets. The decrease in the decomposition of PET into terephthalic acid monomer from the thermal stability of raw materials and waste PET plastic pellets occurs at a temperature of 4500ËšC. This potential finding can be used as a basis for consideration in regions or countries that have the generation of garden waste and plastic, especially the type of PET to be used as an environmentally friendly fuel.